C++ Software Design : Design Principles and Patterns for High-Quality Software - Iglberger, Klaus, ....- (Sebastopol : O'Reilly, 2022)
Good software design is essential for the success of your project, but designing software is hard to do. You need to have a deep understanding of the consequences of design decisions and a good overview of available design alternatives. With this book, experienced C++ developers will get a thorough, practical, and unparalleled overview of software design with this modern language. C++ trainer and consultant Klaus Iglberger explains how you can manage dependencies and abstractions, improve changeability and extensibility of software entities, and apply and implement modern design patterns to help you take advantage of today's possibilities. Software design is the most essential aspect of a software project because it impacts the software's most important properties: maintainability, changeability, and extensibility.
Keywords: C++.; Programmeren